Nursing care in a patient with heroin addiction according to the watson human care model: case report - Doğan, Ufuk; Aslanoğlu, Eren (Journal of Dependence, 2025)
The main purpose of care theories in nursing science is to guide nursing practices and to carry out these practices in a systematic way. Care theories allow nurses to better understand the individual needs of patients and to develop personalised care plans appropriate to these needs. Watson’s Human Care Theory aims to provide nursing services in a humane, compassionate, aesthetic and ethical framework based on this understanding. In the literature, it is known that this theory is used effectively in situations such as chronic diseases and emergencies or traumatic situations (e.g. injury, burns). However, studies directly applying this theory in specific areas such as substance use disorder are quite limited. Our case is a 33-year-old male patient who has been using various substances for 21 years. For the last 3 years, he has been using opiates especially orally (in the form of foil/smoke inhalation). The patient stated that he had serious problems in his family relationships, interpersonal relationships and work life. He applied for inpatient treatment with the support and guidance of his family upon the addition of paranoid thoughts and perceptions of evil in recent months. The case was evaluated holistically with the Human Care Model and significant progress was made in risk awareness, selfassessment skills and efforts to improve social relations. The increase in the individual’s belief in treatment and motivation supported his active participation in the recovery process.